Dr. Armando Sánchez a life dedicated to health (Revista Venezolana de Salud Pública, 2018)
The achievements of Dr. Armando Sánchez, the foundation of the Section (Chair) of Rural Medicine at UCLA, his visit to the Government of the Amazon, the creation of CAICET and other achievements in health are briefly described.
Keywords: Medicine; indigenous rural population; Amazonas; NaWarao